Indicadores de sostenibilidad institucional en la gestión de suelos, hábitat y biodiversidad en el Centro Experimental, academico Salache, Universidad Técnica de Cotopaxi, período 2020 – 2021. - Guanotasig Quishpe, Grace Paola (2021)
The main objective of this work was the elaboration of environmental sustainability indicators in soil, habitat and biodiversity management for the Salache Experimental and Academic Center of the Technical University of Cotopaxi, as a result of this study a proposal for an environmental development plan was generated, the methodology consisted of field data collection for the diagnosis of the current situation of the study area, in addition to the use of manuals such as the ECLAC methodological guide as a source for the proper construction of indicators, the development plan includes activities that will allow the measurement of indicators and their subsequent evaluation. The results obtained from the diagnosis of the current situation included biophysical components such as: soil, climate, water, flora and fauna, land use planning and population, highlighting the green index calculated for the CEASA campus which is 15.25m2 /student, this value exceeds the reference established by the WHO which is 9.00 m2 / inhabitant which favors the sustainability of the campus. These indicators will allow the evaluation of a history of certain characteristics such as the degree of soil erosion, infrastructure construction and biodiversity loss with manageable dimensions and visualizing an expected future result. A development plan was proposed for the project, which includes activities, strategies, the time frame in which they should be carried out, and the people responsible for carrying out each activity. The results obtained show us the current situation of soil erosion, degradation and contamination by chemical and natural agents, the scarce biodiversity and threatened by loss of ecosystems and habitat where there is no evidence of a structured design to be sustainable with the environment and within the campus, based on these results it is concluded that in the aspects mentioned above in Campus, is in a situation susceptible to improvement in the area of sustainability, for which it is advisable to act as a priority on the negative impacts that occur within the three managements and taking into account the indicators developed.